(untitled) (Journal of Global Accounting, 2024)
In the trend of globalization, profit is always a concern for companies because the competition is increasingly fierce. In spite of banking regulation and examination by the Central Bank of Nigeria, Deposit Bank Insurance Corporation, and the Chartered Institute of Bankers of Nigeria, there is still a growing concern about fraud and other unethical practices in the commercial banks. With accounting tools and policies, managers of companies can perform profit management. Thus, the paper seeks to ascertain the effect of pressure on discretionary accruals in deposit money banks in Nigeria. The study employed ex post factor research design and a total of fifteen (15) Commercial Banks listed in the Nigerian Exchange Group from 2019-2023 were sampled. Secondary data was collated even as descriptive statistics and correlation coefficient was used to conduct analysis through SPSS statistical software. Finding made showed that pressure has significant effect on discretionary accruals. It was therefore recommended that Shareholders, Managers and Forensic accountants, should be effective in mitigating pressure in cause of corporate dealings..